O2-S2.04 Targeting HIV prevention efforts on HIV-infected men using conditional cash transfer (CCT): does it work?. (10th July 2011) - Khan, A; Qazi, R; Nazim, N; Khan, A A
Abstract : Background: Preventing HIV infections in female spouses of HIV-infected men is limited by low HIV testing rates among these women who are at an increasingly high risk for HIV acquisition. We explored the effect of conditional cash transfer (CCT) on HIV-infected men for spouse testing and HIV status disclosure to their spouses. Methods: Using medical charts we identified all eligible HIV-infected married men receiving care at the PIMS HIV clinic, Islamabad. Selection criteria for CCT were sexually active married men receiving care >6 months including at least two counselling sessions whose spouses had never been tested for HIV (HIV status unknown). CCT was cash given to cover travel/accommodation (US14 for out-town and US 5 for in-town) costs for bringing the spouse to the HIV clinic for testing. All study participants underwent a brief study questionnaire looking at patient demographics, visit history, factors influencing spouse testing, barriers to care and self-disclosure. The CCT acceptance rate was 90% among HIV-infected men. Outcome of interest was spouse testing and status disclosure to spouse at 6 months post CCT. Results: Of the 230 married men, 138 men (60%) had spouses' never tested/unknown status. Baseline disclosure of HIV status to wife was 29%, and median duration of receiving care was 14.3 months. From these 138 men we were able to contact and enrol 94 (68%) men for CCT; 53 (56%) brought their spouses for HIV testing within 4 months; 19 (20%) self-reported getting their wives tested elsewhere, and only 22 (24%) did not comply with the CCT conditionality. CCT improved disclosure of HIV status from baseline 29% to 62% (p <0.05). Factors associated with spouse testing were men <50 years, high ART compliance score, and prior self-disclosure of status to one family member (p <0.05). Conclusions: Even within the context of a socially conservative society CCT can significantly improve HIV testing rates for female spouses and self-disclosure of HIV status by HIV-infected men. Using CCT for timely prevention of HIV infection in wives and children of HIV positive men reduces risk and can be an effective strategy to overcome socio-cultural and financial barriers. Further studies are needed to explore cost-effectiveness of this approach in preventing new infections.